Hubungan Tingkat Pengetahuan dengan Perilaku Sadari pada Remaja Putri di SMA Negeri 1 Krueng Barona Jaya Aceh Besar Tahun 2025 - Wilza Wilza; Syukriadi Syukriadi; Cut Oktaviana (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Adolescence is a transitional period marked by rapid physical, psychological, and social changes. During this time, hormonal growth occurs as a sign of puberty and the activation of reproductive organs, one of which is breast development. However, these changes can sometimes lead to breast abnormalities such as lumps, pain, or changes in shape that may indicate early signs of health problems. One of the most effective early detection efforts for breast abnormalities is Breast Self-Examination (BSE). This examination is important to be done regularly so that each individual, especially adolescent girls, can recognize the condition of their breasts early on. Unfortunately, many adolescent girls still do not know what BSE is or how to perform it correctly. This study aimed to determine the relationship between the level of knowledge and breast self-examination (BSE) behavior among female students at SMA Negeri 1 Krueng Barona Jaya, Aceh Besar District. This research was a quantitative study using an analytic cross-sectional design. Data collection was carried out on May 27, 2025, with a population of 30 female students from grades X and XI, selected using accidental sampling techniques. Data analysis using the Chi-Square test showed that there was no relationship between knowledge level and BSE behavior, with a p-value of 0.384 (p > 0.05). It is expected that parents and schools can improve adolescent girls’ knowledge about BSE as an effort for prevention and early detection of possible breast abnormalities.